Total Hip Arthroplasty for Hip Fractures: Time to Surgery With Respect to Surgical Revision, Failure, and Mortality. (2nd January 2019) - Müller, Franz; Galler, Michael; Zellner, Michael; Bäuml, Christian; Grechenig, Stephan; Kottmann, Tanja; Füchtmeier, Bernd
Introduction: There are increasing demands to perform surgery of hip fractures without delay. However, few studies have assessed the time to surgery in relation to outcome measurements. Methods: A total of 643 consecutive patients with a minimum age of 60 years underwent total hip arthroplasty (THA) for an intracapsular hip fracture. For this retrospective case series, demographic data and the outcome measurements—(1) any surgical revision, (2) implant failure, and (3) mortality—were documented from a prospective clinical database. The time from admission to surgery was also documented prospectively and then data were divided into 4 groups according to the time of surgery: (1) within 12 hours, (2) >12 to 24 hours, (3) >24 to 48 hours, and (4) later than >48 hours. The study end point was 2 years after surgery. Final evaluation was conducted for any missing data through a telephone interview. Results: The patients comprised 456 women (70.9%) and 187 men (29.1%) with a mean age of 80.2 years (range 60-104 years; standard deviation ±7.4). Descriptive data were without effect in all 4 groups. Time to surgery did not significantly influence revision for any reason ( P = .323), implant failure ( P = .521), and mortality ( P = .643). Cox regression analysis identified male sex ( P < .001; 95% confidence interval (CI), 1.27-2.44), American Society of Anesthesiologists score ≥3 ( P < .001; 95% CI, 2.12-21.59), C-reactive protein level >21 mg/L ( P < .018; 95% CI, 1.09-2.60), hemoglobin level <12.0 g/dL ( P = .033; 95% CI, 1.04-2.68), and dementia ( P < .000; 95% CI, 1.50-2.86) as independent significant risk factors for mortality. Conclusion: Time to surgery had no effect on revision for any reason, implant failure, and mortality in patients undergoing THA for an intracapsular hip fracture.